Novel Biomarkers of Prenatal Methamphetamine Exposure in Human Meconium - Gray, T.; Kelly, Tamsin; LaGasse, L.; Smith, L.; Derauf, C.; Haning, W.; Grant, P.; Shah, R.; Arria, A.; Stauss, A.; Lester, B.; Huestis, M. (Lippincott Williams and Wilkins, 2009)
Meconium analysis can detect fetal exposure to drugs taken by the mother during pregnancy. Methamphetamine (MAMP) and amphetamine (AMP) have previously been observed in meconium of MAMP-exposed neonates; the presence of other metabolites has not been investigated. Detection of such analytes may lead to more sensitive identification and thus improved medical treatment of affected infants. Forty-three MAMP-positive meconium specimens were analyzed for newly identified MAMP biomarkers, p-hydroxymethamphetamine, p-hydroxyamphetamine, and norephedrine. Due to MAMP adulteration in illicit ecstasy and to simultaneously monitor 3,4-methylenedioxymethamphetamine and MAMP prenatal exposure, 3,4-methylenedioxymethamphetamine, its metabolites, and related sympathomimetic amines were assayed. MAMP, AMP, and unconjugated p-hydroxymethamphetamine were the most prevalent and abundant analytes present in meconium; however, unconjugated p-hydroxyamphetamine and norephedrine also were identified. It is possible that one of these additional analytes could be important for predicting toxicity or maternal or neonatal outcome measures in fetuses exposed to MAMP at specific gestational ages or with different metabolic capabilities. Although these new biomarkers were present in lower concentrations than MAMP and AMP in the meconium of previously confirmed specimens, additional research will determine if inclusion of these analytes can increase identification of MAMP-exposed neonates. Novel methamphetamine biomarker concentrations were characterized in meconium of infants exposed in utero to MAMP.